Nanostructured lipid carrier improved in vivo anti-tumor and immunomodulatory effect of Zerumbone in 4T1 challenged mice. Issue 28 (25th February 2015) - Mohamad, Nurul Elyani; Abu, Nadiah; Rahman, Heshu Sulaiman; Ky, Huynh; Ho, Wan Yong; Lim, Kian Lam; How, Chee Wun; Rasedee, Abdullah; Alitheen, Noorjahan Banu; Yeap, Swee Keong
Abstract : Nanostructured lipid carrier (NLC) encapsulation enhanced the in vivo antitumor, antitumor immunity and anti-inflammatory effects of Zerumbone on 4T1 challenged mice. Abstract : Zerumbone is a potential anti-inflammatory, immunomodulatory and anti-tumor agent. However, the major problems that prevent the in vivo and even clinical applications of Zerumbone are its water insolubility that compromises its bioavailability. To enhance the bioavailability and efficacy of Zerumbone, nanostructured lipid carriers (NLC) were used to encapsulate Zerumbone. NLC–Zerumbone has been reported to have a slow release, comparable in vitro cytotoxicity against leukemia and breast cancer, and no observed in vivo oral acute toxicity. However, the in vivo antitumor effect of NLC–Zerumbone is still unknown. The anti-tumor, immunostimulatory and anti-inflammatory effects of Zerumbone and NLC–Zerumbone in 4T1 challenged mice were compared in this study. Zerumbone effectively controlled the tumor growth and metastasis via delaying the cancer cell cycle progression and apoptosis. Besides, Zerumbone also enhanced the anti-tumor immunity and anti-inflammatory effects. NLC encapsulation was found to further improve the anti-tumor, immunomodulation, anti-inflammation and anti-metastatic efficacy of Zerumbone in 4T1 challenged mice. This study provides the possibility of utilizing NLC encapsulated Zerumbone for breast cancer therapy.